2-amino-1-methyl-6-phenylimidazo(4, 5-b) pyridine (PhIP) induces gene expression changes in JAK/STAT and MAPK pathways related to inflammation, diabetes and cancer. Issue 1 (December 2016) - Rogers, Lora; Basnakian, Alexei; Orloff, Mohammed; Ning, Baitang; Yao-Borengasser, Aiwei; Raj, Vinay; Kadlubar, Susan
Abstract Background 2-amino-1-methyl-6-phenylimidazo(4, 5-b)pyridine (PhIP), a heterocyclic aromatic amine (HCA) formed in meat that is cooked at high temperatures and then ingested, can potentially be retained in human adipose tissues. Methods To determine if PhIP is bioactive in the adipocyte, we exposed a human adipocyte cell line, HepG2 and Caco-2 cells to low dose PhIP. Uptake and retention of PhIP was determined and cytotoxicity was assessed by the TUNEL assay. Relative expression of PhIP-activating genes (CYP1A1, CYP1A2, SULT1A1 and UGT1A1) was determined by RT-PCR and global expression changes were also examined. Results The percent retention of 0.1 μCi [14 C]-PhIP over a 24 h period was significantly higher in the adipocyte than the HepG2 (p  = 0.0001) and Caco-2 (p  = 0.0007) cell lines. Cytotoxicity rates were 14.4 and 2.6 % higher compared to controls in Caco-2 and HepG2 cells (p  < 0.001 and 0.054, respectively); no significant differences were detected in adipocyte cells (p  = 0.18). Caco-2 and HepG2 cells, respectively, had significantly higher basal expression of CYP1A1 (p  = 0.001, p  = 0.003), SULT1A1 (p  = 0.04, p  < 0.001) and UGT1A1 (p  < 0.001, p  = 0.01) compared to the adipocyte. Exposure to 5nM PhIP did not significantly induce expression of these genes in any of the cell lines. Global gene expression analysis of mature adipocytes exposed to 5nM PhIP for 72 h resulted in statistically significant changes in 8 genes (ANGPTL2, CD14, CIDEA, EGR1, FOS, IGFBP5, PALM andPSAT1 ). Gene-gene interaction and pathway analysis indicates that PhIP modulates genes controlled by the STAT3 transcriptional factor and initiates leptin signalingvia the JAK/STAT and MAPK pathway cascades. Early growth response 1 (EGR1) and prostaglandin synthase 2 (COX-2) were down-regulatedvia c-Fos, while insulin binding protein 5 (IBP5) was up regulated. Expression of transcription factors (ANGPTL2, HP, LEP, SAA1, SAA2), genes related to inflammation (SAA1, LEP), diabetes (IGFBP5) and cancer risk (SAA2) were also elevated upon exposure to 5 nM PhIP.. Conclusions PhIP mediates gene expression changes within the adipocyte, and the pathways most affected are related to cancer and other chronic diseases. Further studies are needed on the relationship between dietary carcinogens such as PhIP with cancer, obesity and diabetes.